Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.bbr.2009.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of study design variables and their impact on food-maintained operant responding in mice

Abstract: Operant conditioning paradigms are useful for studying factors involved in reward, particularly when combined with the tools of genetic manipulation in mice. Published operant studies involving mice vary widely with respect to design, and insight into the consequences of design choices on performance in mice is limited. Here, we evaluated the impact of five design variables on the performance of inbred male mice in operant tasks involving solid food pellets as reinforcing agents. We found that the use of lever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…Mice required between 5 and 8 days, with an average of 6.3 days, to meet the acquisition criteria. These results are consistent with operant training on commercially sold systems, and the acquisition curves of the reinforced mice were similar to those of mice trained in commercially sold chambers (Haluk and Wickman, 2010;Sharma et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Mice required between 5 and 8 days, with an average of 6.3 days, to meet the acquisition criteria. These results are consistent with operant training on commercially sold systems, and the acquisition curves of the reinforced mice were similar to those of mice trained in commercially sold chambers (Haluk and Wickman, 2010;Sharma et al, 2012).…”
Section: Resultssupporting
confidence: 91%
“…Force requirements for pressing levers, species-specific sensorimotor repertoires and response preferences collectively appear to account for substantial strain-specific differences in the rate of acquisition of lever pressing responses by mice and high variability of performance of operant schedules of tasks using this operandum [11,21,44,55]. However, not all studies support this conclusion [28], suggesting that the utility of lever pressing depends on complex, task- and strain-related variables.…”
Section: Methodsmentioning
confidence: 99%
“…*Acquisition Criteria: The criteria used to determine acquisition of food-maintained operant responding includes: (1) a minimum number of active responses and rewards earned; (2) a measure of discrimination between active and inactive levers, and (3) between-session performance stability. Mice exhibiting discrimination of ≥3:1 for the active versus inactive lever and obtaining ≥ 20 rewards per session over three consecutive sessions are considered to achieve acquisition criteria 10 . We have observed that the majority (~75%) of C57BL6 mice require about 7-10 days of training to achieve acquisition criteria.…”
Section: Operant Trainingmentioning
confidence: 99%